Insight orientation scale: A promising tool for organizational outcomes–A psychometric analysis using item response theory - Gori, Alessio; Topino, Eleonora; Svicher, Andrea; Schuldberg, David; Di Fabio, Annamaria (Frontiers in Psychology, 2022)
Insight is a construct carried out into different theoretical orientations with increasing application out of the boundaries of clinical psychology. Recent studies have investigated insight also as a promising variable for organizational outcomes. Given the relevance of Insight in promoting change, this paper aimed at describing the psychometric analysis of one of the shortest, most agile, and most versatile tool for measuring some of the characteristics of insight, the Insight Orientation Scale (IOS), using Item Response Theory. To achieve this goal, we applied a Mixed Rash Model to the IOS. Data from 1445 individuals were analyzed by the means of WIN-MIRA and Multilog. Based on the likelihood statistics (CAIC) we assumed a three-class solution for the IOS. Results also indicated that the greater part of items had good discrimination and threshold parameters. These findings confirmed psychometric stability of the IOS highlighting its measurement precision, supporting its utility in both research and practice.